Cross-protective efficacy of whole cell and outer membrane protein vaccines of Pasteurella multocida serotype B:2 - WASNIK, R V; SRIVASTAVA, S K; PAUL, A (The Indian Journal of Animal Sciences, 2014)
Immunogenic potential of outer membrane protein (OMP) of Pasteurella multocida serotype B:2 in conferring homologous and cross-protection in laboratory animals, as compared to vaccines consisting of whole cells grown with or without dipyridyl, (DIP) an iron-chelator, was studied. Using slide agglutination test, the antibody titres in pooled sera from rabbits given either of the vaccines increased from day 14 post-vaccination (PV) reaching peak at day 28 or 35. followed by a decline at day 50 and further at day 90 PV. Similar trend was observed when ELISA was employed using puritied OMP or sonicated P. mul/oeida cell antigen. However, in this assay OMP proved to be inore immunogenic than the other 2 vaccines. The vaccinated rabbits when challenged at 1 month and 3 months PV exhibited satisfactory level of protection with OMP vaccine. Among the whole cell vaccines satisfactory protection was observed with and whole cell(grown without dipyridyle) vaccine only. Sera from these rabbits collected at day 28 and 90 PV passively protected mice against the challenge with the homologous P multoeida strain as well as the heterologous serotypes, viz. A:3 and F:3, 4 except 90 PV sera from OMP vaccinated rabbits which did not exhibit satisfactory level of protection against serotype A:3. Among the 3 vaccines, the whole cell (cells grown with DIP) vaccine proved most protective. The study suggested that eithe’r OMP vaccine or whole P. multaeida cell vaccine could be used for conferring cross-protection in animals against P. multocida infection.